Strategies for Strengthening Harmonious Values in the Family from the Perspective of Islamic Family Law - Abdul Wapa; Dul Jalil (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Understanding Islamic family law plays an increasingly important things in shaping individual character and strengthening family values, particularly within the Islamic legal framework. This study aims to describe Islamic family law perspectives on harmonious values and analyze strategies for their implementation in the Kampung Gebang community, Tangerang City. The family in Islam is regarded as a sacred institution and the foundation of a just and moral society, where harmony is aligned with the objectives of maqāṣid al-sharī‘ah which protecting lineage, preserving honor, and fostering peace. Using a qualitative socio-legal approach, the research integrates doctrinal analysis of the Kompilasi Hukum Islam (KHI), Marriage Law No. 1 of 1974, and relevant court decisions with empirical data from interviews, observations, and literature review. Findings reveal several interconnected strategies, including three categories in religious, legal, and sociological. These strategies, while sociological in practice, are deeply rooted in legal norms and obligations, such as parental duties, spousal responsibilities, and mediation procedures mandated by Islamic law and national legislation. Religious Courts reinforce these principles by prioritizing reconciliation and protecting children’s welfare. The study concludes that family harmony in Kampung Gebang is sustained through a balance of moral guidance and enforceable legal frameworks, offering practical insights into bridging normative Islamic law with lived community practice.